2021
DOI: 10.1007/s00429-021-02266-z
|View full text |Cite
|
Sign up to set email alerts
|

Neural representations underlying mental imagery as unveiled by representation similarity analysis

Abstract: It is commonly acknowledged that visual imagery and perception rely on the same content-dependent brain areas in the high-level visual cortex (HVC). However, the way in which our brain processes and organizes previous acquired knowledge to allow the generation of mental images is still a matter of debate. Here, we performed a representation similarity analysis of three previous fMRI experiments conducted in our laboratory to characterize the neural representation underlying imagery and perception of objects, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Albeit several studies (Kosslyn et al, 1995 ; Kosslyn & Thompson, 2003 ; Pearson, 2019 ; Pearson & Kosslyn, 2015 ) have stressed the importance of early visual areas during imagery, subsequent work has led to contradictory findings (Lee et al, 2012 ) emphasizing instead the role of the HVC during imagery. Crucially, beyond the canonical activation analysis, a collection of studies using multivariate analyses (e.g., multivoxel pattern analysis and representational similarity analysis), has revealed that the areas of the HVC play a crucial role during imagery of scenes (Lee et al, 2012 ) and their locations (Boccia et al, 2015 , 2017 , 2021 ). With this in mind, to circumvent the potential difference between the imagery and the visual stimulus, in the DCM analysis, we specified condition‐specific connectivity models including only the scene‐selective and hippocampal regions, together with V1 in the visual perception.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit several studies (Kosslyn et al, 1995 ; Kosslyn & Thompson, 2003 ; Pearson, 2019 ; Pearson & Kosslyn, 2015 ) have stressed the importance of early visual areas during imagery, subsequent work has led to contradictory findings (Lee et al, 2012 ) emphasizing instead the role of the HVC during imagery. Crucially, beyond the canonical activation analysis, a collection of studies using multivariate analyses (e.g., multivoxel pattern analysis and representational similarity analysis), has revealed that the areas of the HVC play a crucial role during imagery of scenes (Lee et al, 2012 ) and their locations (Boccia et al, 2015 , 2017 , 2021 ). With this in mind, to circumvent the potential difference between the imagery and the visual stimulus, in the DCM analysis, we specified condition‐specific connectivity models including only the scene‐selective and hippocampal regions, together with V1 in the visual perception.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in Ragni et al, (2021), with significantly above-chance decoding accuracy observed from the left fusiform face area, the bilateral parahippocampal place area, and frontoparietal regions, but not in early visual cortex regions. Evidence for successful decoding of face imagery from VTC regions has also been demonstrated by Boccia et al (2021) using representational similarity analysis. Results showed that activation patterns in high-level visual areas (ie., bilateral fusiform face area, bilateral occipital face area, and left occipito-place area) could be observed across imagined stimuli categories.…”
Section: Mental Imagery Of Facesmentioning
confidence: 89%
“…Further evidence for the role of regions within the VTC (encompassing the fusiform gyrus / fusiform face area) in face mental imagery stems from the studies using multivariate voxel pattern analysis of fMRI data to decode imagined stimuli from brain activity (Boccia et al, 2021;Ragni et al, 2021;Reddy et al, 2010;VanRullen & Reddy, 2019). For example, Reddy et al (2010) asked participants to either see or imagine stimuli from four domains (shapes, tools, faces, and places) and then estimated activity patterns from object-responsive voxels separately from the perception and imagery tasks.…”
Section: Mental Imagery Of Facesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, some evidence shows a decrease in activity in the occipital cortex during VMI (Kilintari et al, 2016). Second, during voluntary VMI there is consistent activation of frontal and parietal regions (Boccia et al, 2015;Boly et al, 2007;Daselaar et al, 2010;Formisano et al, 2002;Ganis et al, 2004;Gardini et al, 2005;Goebel et al, 1998;Guillot et al, 2009;Kilintari et al, 2016;Kukolja et al, 2006;Logie et al, 2011;Newman et al, 2005;Whittingstall et al, 2014;Zvyagintsev et al, 2013) and of the left hemisphere's fusiform gyrus (Belardinelli et al, 2009;Boccia et al, 2015Boccia et al, , 2021de Volder et al, 2001;D'Esposito et al, 1997;Howard et al, 1998;Hsu et al, 2011;Ishai, 2002;Ishai et al, 2000;Khuvis et al, 2021;Palmiero et al, 2009;Ragni et al, 2021;Reddy et al, 2010;Silson et al, 2019;Slotnick et al, 2005;VanRullen & Reddy, 2019). A meta-analysis of 27 fMRI studies, we (Spagna et al, 2021) defined the boundaries of this region in the mid-fusiform gyrus (Tailarach coordinates: -40, -55, -11) and named it the Fusiform Imagery Node (FIN).…”
Section: Introductionmentioning
confidence: 94%